DIFFERENT WAYS TO EXERCISES AND ACTIVITIES TO IMPROVE THE VOCABULARY OF B2 LEVEL STUDENTS BY READING - Shermamatova Sevaraxon Oʻktamovna; Qaxramonova Gulrux Dilshodbek qizi (TADQIQOTLAR.UZ, 2024)
ANNOTATION: The article talks about how learning new words is important for learning a language, and how reading helps with this. The students we picked are better at reading than usual. So we look closely at the exercises and tasks they do. In addition, we use reading exercises to help students have better vocabulary. This article looks at how reading activities can be used for learning in the 21st century.